Etiology and Management of Bacterial of Anthurium - Dhanya M K (Department of Plant Pathology, College of Agriculture, 2000)
Bacterial blight incited by Xanthomonas axonopodis pv. dieJJenbachiae (Me Culloch and Pirone) Vauterin et al. (1995) is a serious disease of anthurium (Anthurium andreanum Linden) causing heavy economic loss to growers in Kerala. The diseased plants showed both foliar and systemic infections. The bacterium was a Gram negative, motile rod. Morphological, physiological and biochemical characters of the six isolates were same except for some characters like nature and rate of growth, virulence and hydrolysis of starch. The bacterium inciting this disease was identified as Xanthomonas axonopodis pv. dieffenbachiae based on morphological, physiological and biochemical characters coupled with pathogenicity. Potato Sucrose Agar was found to be the best medium for growth and slime production of the bacterium. Dieffenbachia sp., Philodendron oxycardium, Aglaonema robelinii, Colocasia esculenta and Syngonium podophyllum were carriers of Xanthomonas axonopodis pv. dieJJenbachiae. The pathogen survived In infected plant debris kept in soil under glass house conditions and In refrigerated conditions for about 45 days and in soil for 60 days. Under in vitro evaluation, 100 ppm streptocycline and 0.3 per cent captan were most effective in inhibiting the growth of the pathogen.